2000
DOI: 10.1093/intimm/12.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of anti-erythrocyte autoantibodies and splenomegaly in autoimmune hemolytic anemia-prone New Zealand Black mice

Abstract: New Zealand Black (NZB) mice spontaneously produce anti-erythrocyte autoantibodies (AEA) in association with splenomegaly, thus serving as a model for autoimmune hemolytic anemia. Although these autoimmune traits are inherited as a dominant fashion, expression in F(1) hybrids of NZB and most non-New Zealand strains is suppressed due to the contribution of wild-type modifying genes present in the latter strains. Using chromosomal microsatellite markers in the (C57BL/6 x NZB)F(1) x NZB backcross progeny, we mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…[17][18][19][20]. In particular, a couple of loci on mouse chromosome 4 have been identified by several investigators to be linked to autoantibody production or other features of B cell hyperactivity (21)(22)(23)(24)(25)(26)(27)(28). When 1 of these loci, Sle2 of NZM2410/NZW origin, was introgressed onto the normal C57BL/6 (B6) background, it precipitated several B cell phenotypes including polyclonal hypergammaglobulinemia and elevated B1 cell formation (29)(30)(31).…”
mentioning
confidence: 99%
“…[17][18][19][20]. In particular, a couple of loci on mouse chromosome 4 have been identified by several investigators to be linked to autoantibody production or other features of B cell hyperactivity (21)(22)(23)(24)(25)(26)(27)(28). When 1 of these loci, Sle2 of NZM2410/NZW origin, was introgressed onto the normal C57BL/6 (B6) background, it precipitated several B cell phenotypes including polyclonal hypergammaglobulinemia and elevated B1 cell formation (29)(30)(31).…”
mentioning
confidence: 99%
“…However, other QTL that map to the 80-90 Mbp chromosome 4 interval include loci that control the immune response (Ifa and Ifb), splenomegaly (Sbw2, Orgwg6 and Spm1), and anti-red blood cell IgG antibodies (Arigg3), which have been implicated in mouse models of autoimmune haemolytic anaemia and systemic lupus erythrematosus [7][8][9]. Significantly, a mouse anti-erythrocyte autoantibody modifier locus (Aem3) and anti-nuclear autoantibody locus (Bana2) co-localise to the suggestive E/NE bone marrow cell ratio QTL on chromosome 10, and a human haematocrit level QTL has also been mapped to chromosome 6q23-24, syntenic to mouse chromosome 10 QTL [1].…”
Section: Discussionmentioning
confidence: 99%
“…For example, QTL that are linked to anti-red blood cell and antinuclear antibody production and splenomegaly have been mapped in mouse models of AHA and SLE [7][8][9]. Similarly, QTL have been identified that determine mouse stem, progenitor and mature white blood cell numbers [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Loci from NZB/NZW crosses are designated Nba, Sle, and Lbw (47,54,55,59,60,74). HA loci from NZB crosses are designated Aem (75). Loci from BXSB crosses are designated Bxs (53,56,80).…”
Section: Discussionmentioning
confidence: 99%